2021
DOI: 10.3390/ijms22094604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Glucose Concentration on Pericyte-Like Differentiated Human Adipose-Derived Mesenchymal Stem Cells

Abstract: A pericyte-like differentiation of human adipose-derived mesenchymal stem cells (ASCs) was tested in in vitro experiments for possible therapeutic applications in cases of diabetic retinopathy (DR) to replace irreversibly lost pericytes. For this purpose, pericyte-like ASCs were obtained after their growth in a specific pericyte medium. They were then cultured in high glucose conditions to mimic the altered microenvironment of a diabetic eye. Several parameters were monitored, especially those particularly aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“…Reactive oxygen species (ROS) were measured by means of the DCFDA—Cellular Reactive Oxygen Species Detection Assay Kit (ab113851, Abcam Cambridge, UK), according to the manufacturer’s protocol [ 27 ]. After the treatments, HREC were incubated with 25 μM 2′,7′-dichlorodihydrofluorescein diacetate (DCFDA) in a buffer solution at 37 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Reactive oxygen species (ROS) were measured by means of the DCFDA—Cellular Reactive Oxygen Species Detection Assay Kit (ab113851, Abcam Cambridge, UK), according to the manufacturer’s protocol [ 27 ]. After the treatments, HREC were incubated with 25 μM 2′,7′-dichlorodihydrofluorescein diacetate (DCFDA) in a buffer solution at 37 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have found that ASCs can differentiate into pericytes and participate in the fixation of early vasculopathy. In vitro studies show that ASCs can express pericyte-specific markers [38,43,44]. In vivo tests further confirmed that ASCs can migrate and integrate with retinal vasculature, adopting the typical pericyte morphological and functional behaviors [38,43].…”
Section: Ascsmentioning
confidence: 73%
“…As a potential treatment for diabetes complication, ASCs displayed stable phenotype and proliferation in a high-glucose environment in multiple in vitro studies. Compared with human retinal pericytes, hyperglycemia has no impact on the adhesion and proliferation of ASCs, indicating them as favorable treatment options for DR patients [38,44,49]. Pro-angiogenic factors are found to be secreted by ASCs, which can be beneficial in reforming healthy and intact vasculatures in early DR.…”
Section: Ascsmentioning
confidence: 99%
“…However, the beneficial effect of AT-MSCs on angiogenesis may be related not only with their paracrine activity but also with their differentiation potential towards pericyte-like cells, which play an important role in stabilization of the vessel wall and prevent vascular leakage. These observations performed in vitro both in normal culture conditions and in high glucose concentration medium, to mimic the changed microenvironment of a diabetic eye, revealed that pericyte-like differentiation of human AT-MSCs can serve as a possible therapeutic option in patients of diabetic retinopathy to replace irreversibly lost pericytes [ 61 , 62 ]. A very recent studies of Beloglazova et al (2022) shows evidence that AT-MSCs support endothelial cell network through the uPA pathway (uPA-uPAR/VEGFR2/integrin/NOTCH).…”
Section: Effect Of At-mscs On Angiogenic Processesmentioning
confidence: 99%